2022
DOI: 10.52250/bmr.v11i1.503
|View full text |Cite
|
Sign up to set email alerts
|

The THE INFLUENCE OF EASE OF USE, E-SERVICE QUALITY AND PERCEIVED USEFULNESS AS AN INTERVENING VARIABLE AN INTENTION TO REUSE ZALORA ONLINE FASHION APPLICATION

Abstract: This study aims to analyze (1) the effect of ease of use on perceived usefulness on Zalora users. (2) The effect of e-service quality on perceived usefulness on Zalora users. (3) The effect of ease of use on intention to reuse on Zalora users. (4) The effect of e-service quality on intention to reuse of Zalora users. (5) The effect of perceived usefulness on intention to reuse on Zalora users. The population on this study is Zalora users who had shopped more than once. The total sample of this research was 224… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Service quality can be conceptualized as the holistic assessment made by consumers regarding the performance of a service provided inside the market (Zehir and Narcıkara, 2016). Pratiwi et al (2022) and Farhadi and Maroosi (2022) found that service quality significantly influences perceived usefulness and perceived ease of use. Thus, the hypotheses related to service quality are as follows:…”
Section: Service Qualitymentioning
confidence: 99%
“…Service quality can be conceptualized as the holistic assessment made by consumers regarding the performance of a service provided inside the market (Zehir and Narcıkara, 2016). Pratiwi et al (2022) and Farhadi and Maroosi (2022) found that service quality significantly influences perceived usefulness and perceived ease of use. Thus, the hypotheses related to service quality are as follows:…”
Section: Service Qualitymentioning
confidence: 99%
“…Jika pengguna memiliki anggapan positif terhadap layanan suatu teknologi saat menggunakan akan menganggap teknologi tersebut mudah digunakan. Penelitian lain didukung oleh Pratiwi et al, (2022).…”
Section: Hubungan Perceived Ease Of Use Pada Perceived Usefulnessunclassified